The Relationship between Cadmium-Related Gene Sequence Variations in Rice and Cadmium Accumulation - Weixing Li; Feng Xu; Tingting Cai; Wanling Zhao; Jianting Lin; Jiayu Huang; Liguo Wang; Jianmin Bian; Junru Fu; Linjuan Ouyang; Yicong Cai; Haohua He; et al. (Agronomy, 2023)
Cadmium (Cd) pollution and uptake into the grains of developing rice plants represent a major threat to human health. Studies of specific genes can offer new insights into the functional roles of particular genes, highlighting candidate alleles that can be leveraged as DNA markers. Accordingly, the identification of novel Cd-related traits and sequence variants can provide new molecular markers for Cd resistance in rice. In the present study, a genetic diversity analysis was carried out on 85 rice varieties exhibiting varied Cd accumulation, and 436 single polymorphic sites (SNP) corresponding to 43 haplotypes were detected across 12 Cd-associated genes (CAL1, OsCADT1, Oscd1, OsHMA4, OsHMA9, OsNRAMP1, OsNRAMP2, OsNRAMP5, OsHMA2, OsHSMA3, OsPCR1, and OsABCG43). By utilizing the information of the SNPs, 85 rice varieties was classified the into 2 clusters with different source categories and Cd contents. Among the variants, 45 sites in 5 genes were significantly associated with the Cd content in rice grains, of which 8 alleles in OsPCR1, CAL1, and Oscd1 were negatively correlated with Cd accumulation. The results of haplotype aggregation analysis for OsPCR1, Oscd1, and CAL1 showed that 85 rice varieties were divided into 5 clusters. Interestingly, most of the varieties in Cluster A belonged to tropical type, which contained the aggregation of three favorable alleles, whereas the temperate varieties constituted the majority of Cluster B lacking favorable alleles. This observation suggests that the allelic combination found in tropical rice varieties may hold promise for reducing Cd accumulation levels in rice grains. The Cd-associated alleles identified in the present study can not only be used to check the Cd tolerance of rice varieties, but also serve as functional molecular markers to differentiate the source of the rice varieties, which provides a better understanding of the relationship between the sequence variation in Cd-related genes and Cd accumulation in rice.